MANAGEMENT OF ISLAMIC EDUCATION: THE CONCEPT OF PLANNING REVIEWED IN THE VERSES OF THE QUR'AN - Harahap, Khoirul Saleh; Rambe, Ali Sanusi; Putra, Ade Putra (Almufida : Jurnal Ilmu-Ilmu Keislaman, 2023)
The planning function greatly influences the achievement of targets and is the earliest stage of achievement measurement. As a guide for Muslims, the Qur'an teaches about the whole meaning of planning. The purpose of this study is to examine the notion of planning as contained in the verses of the Qur'an. Qualitative analytical descriptive research is used as an approach. This information was collected through a literature survey and study of the Qur'anic text. It is also examined using reduction procedures, displaying data, and making inferences or validating results. According to the findings of this study, the role of planning is very important in the management function of Islam. Because planning is the initial step or technique used to achieve a goal, the Qur'an explains several planning principles so that it becomes a guide for humans to carry out a plan to achieve the goals or objectives that have been prepared. This article discusses the topic of planning in the Qur'an, specifically Surah Al-Anfal: 60.